Ultrasound assessment of botulinum toxin-A (BOTOX) injection into adult Arabian dromedary camels’ lips: efficacy in detection and localization - Marzok, Mohamed; Hussen, Jamal; Al Dhafiri, Mahdi; Saleh, Sherif; El-Husseiny, Hussein M.; El-Sherif, Mohamed W.; Ayman al wail, Abdullah; Almubarak, Adel I.; Salem, Mohamed (BMC veterinary research, 2025)
Ultrasound imaging has become an invaluable tool in veterinary medicine, particularly in guiding injections and visualizing soft tissue structures. Recently, ultrasonography has been used in camel practice to detect cosmetic fillers, particularly in aesthetic evaluations. However, previous applications lacked a controlled experimental background. This study is the first to experimentally assess the effectiveness of ultrasound in detecting and localizing botulinum toxin (BOTOX) injections in camels, using two different doses, from the time of injection until the toxin's effect becomes undetectable. The objective of this study was to assess the efficacy of ultrasound in detecting and localizing botulinum toxin injection sites in camels' lips. This study involved 18 adult Arabian dromedary camels (9 Magateer and 9 Majaheem breeds) from the Camel Research Center, King Faisal University. The camels, aged 4.3 ± 1.3 years and weighing 405.5 ± 20.6 kg, were randomly assigned to three treatment groups (6 camels each). Treatments included 100 IU and 200 IU of botulinum toxin type A, and a control of 5 ml sterile saline, administered to the upper and lower lips. Morphological changes, inflammation, and lip thickness were assessed weekly for two months. Ultrasound examinations and hematological and biochemical analyses were conducted at specified intervals. Data were analyzed using two-way repeated-measures ANOVA and Tukey's test, with significance set at p < 0.05. Morphological assessments revealed significant changes in the lips of camels treated with 200 IU BOTOX, showing the highest shape change scores (3 ± 0) compared to 100 IU BOTOX (1.75 ± 0.87) and control (0.4 ± 0). Inflammation and tissue reactions were more pronounced in the BOTOX-treated groups, with higher scores in the 200 IU group. Lip thickness increased significantly in the BOTOX groups, with the greatest thickening in the 200 IU group (2.4 ± 0.54 mm). Ultrasonographic findings showed structural changes and increased tissue thickness, peaking on Day 7 and gradually normalizing by Day 54. Hematological and biochemical profiles showed no significant differences between the treated and control groups. The study demonstrates the effect of BOTOX on camel lip morphology and tissue characteristics, with higher doses (200 IU) causing more significant and prolonged changes. Both morphological scoring and ultrasonographic evaluation effectively monitored these effects, including the timeframe of BOTOX detection and when it became undetectable.